Pancreatic Adenocarcinoma Producing Parathyroid Hormone-Related Protein - Reiko Yamada; Kyosuke Tanaka; Hiroyuki Inoue; Takashi Sakuno; Tetsuro Harada; Naohiko Yoshizawa; Hiroshi Miura; Toshihumi Takeuchi; Misaki Nakamura; Masaki Katsurahara; Yasuhiko Hamada; Noriyuki Horiki; et al. (Case Reports in Oncological Medicine)
A 48-year-old woman presented to our hospital with a 1-year history of a continuous high fever. She was diagnosed with metastatic pancreatic adenocarcinoma accompanied by leukocytosis without infection. Her serum concentration of granulocyte colony-stimulating factor was highly elevated. Forty-five days after initiating chemotherapy, she was readmitted because of a neuropsychiatric disturbance and hypercalcemia. Her serum concentration of parathyroid hormone-related protein (PTH-rP) was elevated. A pretreatment biopsy specimen showed strong cytoplasmic immunoreactivity to anti-PTH-rP antibody, suggesting that overproduction of PTH-rP accounted for the hypercalcemia. Although the patient regained consciousness after treatment, she died of progressive disease 60 days after chemotherapy.